Successful use of anifrolumab in refractory cutaneous lupus erythematosus with systemic lupus erythematosus: A case report - Abdullah Ramadhan; Anita Troung; Elaine Yacyshyn; Robert Gniadecki (SAGE Open Medical Case Reports, 2025)
A 61-year-old female with systemic lupus erythematosus presented with refractory discoid lupus. Despite treatment with numerous immunosuppressive therapies, including prednisone, hydroxychloroquine and mycophenolate mofetil, her cutaneous lupus remained active and significantly impacted her quality of life. Introduction of anifrolumab led to remarkable improvement, highlighting its potential for refractory discoid lupus erythematosus.